Aspects of medical waste disposal in the Cape Peninsula - Tolosana, Sandra (Department of Public Health and Family Medicine, 2017)
Hazardous waste management practices at ten medical institutions in Cape Town were studied and tests undertaken to determine concentrations of specific chemicals and radioactivity in liquid effluent outflows, as well as emissions from incinerators. To investigate the sewage outflow for Chemical Oxygen Demand (COD), N, pH and heavy metals, a continuous sampler was installed at two hospitals and a Medical School. Samples were analysed by atomic absorption spectrometry for As, Hg, Cd, Co, Cr, Cu, Mn, Ni, Pb, Zn and Fe. Mercury levels ranged from l-70μg l⁻¹, exceeding the Environmental Target Quality of 0.04μg l⁻¹, and the South African General Effluent Standard of 20μg l⁻¹ . All other heavy metals were below General Effluent Standard Limits. In addition, a sludge sample from the Athlone Wastewater Plant was tested for Hg, realising 6mg kg⁻¹ on a dry weight basis, which was within Department of Health (DOH) Guidelines of 10 mg kg⁻¹. Samples of incinerator bottom ash analysed for heavy metal content gave Hg concentrations of 1.1-4.0mg kg⁻¹, and Zn concentrations of 5.1-11.0g kg⁻¹. Incinerator ash was also analysed for radio-activity and substantial levels of ¹²⁵I (332-650 bq kg⁻¹ ), and Ga⁶⁷ (9186bq kg⁻¹) recorded, which exceeded the South African limits of 200bq kg⁻¹. In Cape Town, hospital incinerators are old, burn large amounts of plastics and produce toxic emissions. They are all situated in residential or inner-city areas, and even though there is legislation dealing with emissions and chemical waste, these laws are not being enforced. Based on the above results, an investigation was carried out to assess attitudes to and knowledge of hazardous waste in the ten institutions. One thousand questionnaires were administered to staff, and the data from the 80% response rate statistically analysed. Results suggest that there is an urgent need for an holistic approach to toxic waste management, encompassing enforceable legislation coupled with on-going educational programmes and strong support from top management and all levels of staff.